How Educational, Economic, and Cultural Resources Do Matter: Cohort Differences in the Impact of Parental Resources on Educational Attainment in the Socialist and Post-Socialist Contexts. Issue 2 (1st April 2021) - Helemäe, Jelena; Saar, Ellu; Lauri, Triin
Abstract: The paper concentrates on the ways the interplay of parental economic, educational, and cultural resources in the intergenerational transmission of educational attainment has changed due to the marketization of post-socialist societies and educational systems. We combine two different approaches: a variable-based regression analysis and a case-based qualitative comparative analysis (QCA). The analysis is based on the European Union Statistics on Income and Living Conditions (EU-SILC) 2011 and concentrates on Estonia. The results indicate that parental educational and cultural resources, manifested in a large home library, enhance children's attainment of higher education. It does so not only in post-socialist Estonia but also during the socialist period despite the Soviet educational system being designed explicitly to eliminate social privilege. Comparison of cohorts who attained higher education during the mid-socialist, late-socialist, and post-socialist periods shows that for all of them common combination with high level of all considered parental resources is highly effective in securing attainment of higher education. In addition to that common effective combination of parental resources, each cohort has its own particular combination of parental resources that effectively enabled attainment of higher education. The influence of the resources that the family deploys tends to accumulate instead of being a compensation channel that conveys parental influence on education. Regression analysis and QCA are complementary: The former allows assessment of the net impact of each individual parental resource on attainment of higher education. The latter reveals the differential impact of individual resources depending of their configurations.